Teaching materials development of role-play game-enhanced English vocabulary acquisition in primary school - Ahmad Talib; Abdullah Abdullah; Mayong Maman (International Journal of Humanities and Innovation (IJHI), 2023)
This research aims to develop teaching materials using role-play game-enhanced English vocabulary acquisition in primary school. This research was conducted in one of the outstanding primary schools in Makassar, South Sulawesi, Indonesia. This study is formative research—developmental research to improve design theory for designing teaching practices or processes. The development of the material was based on three important steps: preliminary study, development, and validation by experts in learning and teaching materials. Before developing the teaching materials, the syllabus should be made to support the development of the teaching materials. The teaching material was developed based on the teaching objectives with the topics or themes related to the student's daily life. After developing the material, the material was evaluated by two experts in learning and teaching materials. The evaluation was done by giving the prototype of the teaching material and validation sheet to the experts. The result of the study is the teaching material of basic English vocabulary based on the role-play technique for the pupils. It was found that this developed material was categorized as good based on the evaluation of the experts of the learning materials. The basic English vocabulary teaching materials, lesson plans, and teaching materials were designed based on the needs of the students. It was discovered after analyzing the data. It is intended that because the contents of the materials apply to the student's everyday lives, they can read and comprehend them. Role-playing techniques are also used in the creation of instructional materials. For the pupils, this technique is engaging and enjoyable. However, the teaching material still needs to be developed regarding the content, language use, and appearance.